Anegdota i epizod jako przykłady analogii precedensu - Gołębiewska, Maria (Prace Polonistyczne, 2023)
What serves as a starting point for the article are theses regarding the analogy in legal acts and regulations – the rule analogy and the precedent analogy. What in turn serves as its point of reference are theses concerning cultural schematization, which include narrative patterns of myth, general (universal) history, and individual history. The legal rule and precedent analogies may be considered as argumentative and narrative strategies. The precedent analogy plays an important role in contemporary, modernist, individualized biographical and autobiographical micronarratives. In fact, the anecdote and the episode may be examined as examples of the precedent analogy. In the contemporary humanities, as well as in the social sciences, the presence of “travelling concepts” has been observed (Mieke Bal). The “episode” and the “anecdote” can be seen as examples of this inter- and trans-disciplinary concept. With this in mind, the article poses questions regarding the argumentation that refers the anecdotal and the episodic in microhistories, especially in particular, individual histories, and, above all, in subjective (auto)biographies. The terms “episode” and “anecdote” pertain to two different modes of describing that which is instant, short-lived, and seemingly included in the allegedly coherent historical whole. The former refers to an extraordinary event that constitutes a breach and disrupts the much sought-after temporal and semantic coherence which helps givemeaning to events. The anecdote, by contrast, confirms this coherence (which includes alleged historical purposefulness and necessity) along with a revealed sense. What serves as a crucial context for the reflections presented in the article is the theory put forward by Max van Manen in Phenomenology of Practice. Meaning-Giving Methods in Phenomenological Research and Writing. In his applied phenomenology, van Manen proposes an argumentative reference to the history of an individual subject – to biography, which he recognizes not only as a documentary testimony to individual existence, but also as an “anecdote” – an example of a general subjective attitude.